Fake News Detection: A Survey - Divya, Divya; Mehala, N (International Journal of Computer Sciences and Engineering, 2025)
Social media plays a vital role in online news circulation due to its ease of access, low cost, swift diffusion of information. The news or information can be of any topic, propagated in multiple modalities. Because of the huge amount of information exchange through online or through different social media platforms such as Facebook, twitter, differentiating true news from the low quality news that leads to the problem of fake news, which may affect the individual or the growth of the society, has become a challenging task. This calls for identification and filtering of fake news. In this paper our focus is on exploring the existing methods or approaches on content (i.e. text) based fake news identification, existing standard data sets, evaluation metric(s), tools and future scope, which helps the researchers to turn up with different and efficient approaches to identify fake news.